Seroprevalence and Molecular Detection of Foot and Mouth Disease Virus in Dairy Cattle Around Addis Ababa, Central Ethiopia - Awel SM (Dove Medical Press, 2021)
Shazali Mohammed Awel,1,2 Getachew Mulatu Dilba,3 Bruk Abraha,2 Demeke Zewde,4 Bayeta Senbata Wakjira,4 Abde Aliy4 1Jigjiga University, College of Veterinary Medicine, Jigjiga, Ethiopia; 2Haramaya University, College of Veterinary Medicine, Dire Dawa, Ethiopia; 3Ambo University, College of Agriculture and Veterinary Science, Department of Veterinary Laboratory Technology, Ambo, Oromia, Ethiopia; 4National Animal Health Diagnostic and Investigation Center, Sebeta, EthiopiaCorrespondence: Getachew Mulatu DilbaAmbo University, College of Agriculture and Veterinary Science, Department of Veterinary Laboratory Technology, P.O. Box:19, Ambo, Oromia, EthiopiaTel +251-912717217Email getachew.mulatu@ambou.edu.etBackground: Foot and mouth disease is a debilitating and highly contagious transboundary disease of cattle that can cause a huge economical loss globally. It is a notifiable disease in Ethiopia, and it is thought to be causing a decrease in cattle productivity and production.Methods: A cross-sectional study and outbreak investigation were performed to estimate seroprevalence, identify associated factors and serotypes of FMDV in dairy cattle around Addis Ababa. A multi-stage random sampling technique was employed for the selection of sampling units for the seroprevalence study. A total of 383 blood samples were collected using plain vacutainer tubes and the obtained sera were tested by 3ABC-Ab ELISA at the NAHDIC lab. Also, from outbreak cases, 20 epithelial tissue samples were collected purposively for the molecular detection of FMDV serotypes.Results: The overall seroprevalence of FMD in dairy cattle was 72.1% (95% CI=67.27– 76.50). The seroprevalence in dairy cattle of Ada Berga, Holeta, and Sululta districts was 97.2%, 71.4%, and 57.6%, respectively. Up on Chi-square analysis, age, body condition, and management system were significantly associated with FMD seroprevalence (p< 0.05). Besides, multivariable logistic regression analysis showed that district, age, body condition, and management were significantly associated with FMD seroprevalence (p< 0.05). The odds of being seropositive to FMD were 6.9 (95% CI=1.8– 24.9; p=0.005) and 2.3 (95% CI=1.2– 4.7; p=0.01) times higher in cattle found in Ada Berga and Holeta Woreda. From outbreak cases, 18 (90.0%) were identified positive for FMDV serotype O.Conclusion: The current study revealed higher seroprevalence was recorded in the study area and associated risk factors identified statically, serotype O of FMDV was identified from outbreak cases. Therefore, it is critical to design and implement feasible control and prevention mechanisms based on the type of circulating virus serotype.Keywords: central Ethiopia, dairy cattle, FMD virus, molecular detection, seroprevalence